Retrospective evaluation of 300 stabbed cases in Elazığ - Tokdemir, Mehmet; Küçüker, Hüdaverdi; Dirol, Fatih (Fırat University, 2001)
In this study we aimed at demonstrating epidemiological features of stab-wound cases, which was consisted 300 of 5060 total forensic cases and were conclusively reported by Elazığ Forensic Medicine Council during April 1997-July 2000. It was striking to find that 38.3% and 33% of all cases involved teenager (10-19 years) and young adults (20-29 years), respectively. High incidences of teenagers facing serious violent attacks like stab-wounds during their early youth period negatively affects individuals when they are in the period of psychosocial devolopment. Therefore we concluded that there is need for implementation of tighter control of related institutions / organisation and media must be more sensitive towards education of society regarding issue.

Bu çalışmada, Nisan 1997- Temmuz 2000 tarihleri arasında Elazığ Adli Tıp Şube Müdürlüğünce muayenesi yapılarak, kati raporları düzenlenen 5060 olgudan 300'ünü oluşturan kesici-delici yaralanmalarının epidemiyolojik özelliklerinin ortaya konması amaçlandı.Olguların %38.3'ünü 10-19 yaş grubundaki çocuk/ergenler, %33.0'ını 20-29 genç erişkinlerin oluşturması dikkati çekmektedir. Kesici-delici alet yaralanması gibi ciddi şiddet eylemlerine maruz kalma oranının çocuk/ergen mağdurlarda yüksek olması, psikososyal gelişim döneminde olan bu bireyleri olumsuz olarak etkilemektedir. Bu nedenle ilgili kurum/kuruluşların denetimlerini sıklaştırması ve basının toplumun eğitimi konusunda duyarlı olması gerektiği kanaatine varılmıştır.
ELAZIĞ'DA 300 KESİCİ-DELİCİ ALET YARALANMASI OLGUSUNUN RETROSPEKTİF OLARAK DEĞERLENDİRİLMESİ